Melanoma Plasticity: Promoter of Metastasis and Resistance to Therapy - Huang, Fan; Santinon, François; Flores González, Raúl Ernesto; del Rincón, Sonia V. (Frontiers in Oncology, 2021)
Melanoma is the deadliest form of skin cancer. Although targeted therapies and immunotherapies have revolutionized the treatment of metastatic melanoma, most patients are not cured. Therapy resistance remains a significant clinical challenge. Melanoma comprises phenotypically distinct subpopulations of cells, exhibiting distinct gene signatures leading to tumor heterogeneity and favoring therapeutic resistance. Cellular plasticity in melanoma is referred to as phenotype switching. Regardless of their genomic classification, melanomas switch from a proliferative and differentiated phenotype to an invasive, dedifferentiated and often therapy-resistant state. In this review we discuss potential mechanisms underpinning melanoma phenotype switching, how this cellular plasticity contributes to resistance to both targeted therapies and immunotherapies. Finally, we highlight novel strategies to target plasticity and their potential clinical impact in melanoma.